Early‐onset acral basal cell carcinomas in Gorlin syndrome. (1st November 2014) - Torrelo, A.; Vicente, A.; Navarro, L.; Planaguma, M.; Bueno, E.; González‐Sarmiento, R.; Hernández‐Martín, A.; Noguera‐Morel, L.; Requena, L.; Colmenero, I.; Parareda, A.; González‐Enseñat, M.A.; et al.
Summary: Two patients are reported in whom early‐onset, distal papules with a histopathological diagnosis of basal cell carcinoma were the first manifestation of Gorlin syndrome (GS). These lesions showed no progression and remained stable through follow‐up. Two different PTCH1 gene mutations were detected in the two patients, and thus a phenotype–genotype correlation of this manifestation of GS was not possible.